2010
DOI: 10.1111/j.1365-2125.2010.03734.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of mycophenolic acid in children and young people undergoing blood or marrow and solid organ transplantation

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS PROJECT? • Mycophenolate mofetil (MMF) is an immunosuppressant drug used for the treatment and prevention of graft vs. host disease in blood or marrow transplantation and acute graft rejection in solid organ transplantation. • Mycophenolic acid (MPA) pharmacokinetics have not been thoroughly studied in paediatric blood or marrow transplant recipients and guidance for optimal dosing of mycophenolic acid in children is lacking. • Mycophenolic acid exhibits considerable inter‐ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(85 citation statements)
references
References 44 publications
3
81
1
Order By: Relevance
“…Assessing adherence to mycophenolate after transplant using plasma MPA concentration has been reported in the literature; however, in the present study assessment of patient adherence using this approach also involved PopPK modelling, adding to the robustness of the technique. Published research on the PopPK of MPA in children has been reported previously . The clearance model developed by Zeng et al (2010) was selected as the most suitable model for the use in the present population of children as the latter model includes concomitant use of cyclosporine or tacrolimus as covariates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessing adherence to mycophenolate after transplant using plasma MPA concentration has been reported in the literature; however, in the present study assessment of patient adherence using this approach also involved PopPK modelling, adding to the robustness of the technique. Published research on the PopPK of MPA in children has been reported previously . The clearance model developed by Zeng et al (2010) was selected as the most suitable model for the use in the present population of children as the latter model includes concomitant use of cyclosporine or tacrolimus as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Published research on the PopPK of MPA in children has been reported previously . The clearance model developed by Zeng et al (2010) was selected as the most suitable model for the use in the present population of children as the latter model includes concomitant use of cyclosporine or tacrolimus as covariates. The results also illustrated the utility of using the DBS sampling approach to assess adherence to mycophenolate, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the same dose kg −1 does not result in the same circulating concentration because the absorption/metabolism/clearance is different.’ Two further papers in the current issue support relatively straightforward approaches. Zeng and colleagues studied the population pharmacokinetics of mycophenolic acid in children undergoing marrow and solid organ transplantation [13]. Body weight and concomitant ciclosporin treatment influenced the pharmacokinetics, and current dosing strategies may be suboptimal for children weighing <10 kg.…”
Section: How Different Are Children?mentioning
confidence: 99%
“…Significant inter- and intrapatient variability of MPA pharmacokinetics provides the basis for therapeutic drug monitoring (TDM) in the case of MMF; however, its importance is still being discussed [ 1 ]. In the literature, studies of MPA pharmacokinetics concern mainly children after transplantation [ 7 , 8 , 9 , 10 , 11 ]. However, in our previous study [ 12 ], in children with nephrotic syndrome, we observed higher trough MPA concentration (C trough ) and area under the time-concentration curve (AUC) if compared to recommended C trough and AUC for transplant recipients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%